Knowledge, attitude, practice of parents with typically developing children on inclusive education - Antolin, Christine Joy C; de Robles, Erika R.
Inclusive education is an emerging principle that provides all children regardless of race, language, religion, gender, and ability, an individualized and quality education without discrimination. The education of young learners are being facilitated by the decisions and influence of their parents. The role of parents with typically developing children in the practice of inclusive education (IE) provides insight on its diversity and how it can be improved in the context of our education system. This study aims to delve deeper into the knowledge, attitudes, and practices of parents with typically developing children on inclusive education. The research method used in this study is a semi-structured, in-depth interview that employs a qualitative approach in its discussion. Data gathered on this research were analyzed using thematic analysis. The study revealed four important conclusions: knowledge gap on inclusive education affects their participation in IE practices; conditional factors or barriers have an impact on the attitudes of the parents towards IE; attitudes towards IE does not reflect their practices; and knowledge, attitude, and practice are important in the promotion of IE.